1994
DOI: 10.1139/f94-234
|View full text |Cite
|
Sign up to set email alerts
|

Cladocera Community Response to Experimental Eutrophication in Lake 227 as Recorded in Laminated Sediments

Abstract: The response of pelagic zooplankton to experimental fertilization was compared with the fossil record of Cladocera obtained from the annually laminated sediments of Lake 227, Experimental Lakes Area, northwestern Ontario. Constrained cluster analysis of both total fossil Cladocera and littoral chydorid communities clearly distinguished between pre- and post-eutrophication communities and further differentiated between years of high and low nitrogen:phosphorus fertilization ratios. However, there were few chydo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…However, common patterns can be highlighted. These studies consistently showed that taphonomic processes do not operate equally between zooplankton taxa (Frey, 1960;Hann et al, 1994;Rautio et al, 2000), since cladoceran exoskeletons, in contrast to copepods and rotifers, are well-preserved in lake sediments. Preservation of remains might even differ among cladoceran species with Bosmina and chydorid well represented by different body part (Frey, 1988) in contrast to Daphnia which are usually under-represented in sediment samples compared to Bosmina (Frey, 1960;Kattel et al, 2007;Kattel, 2009;Nykänen et al, 2009).…”
Section: Introductionmentioning
confidence: 83%
“…However, common patterns can be highlighted. These studies consistently showed that taphonomic processes do not operate equally between zooplankton taxa (Frey, 1960;Hann et al, 1994;Rautio et al, 2000), since cladoceran exoskeletons, in contrast to copepods and rotifers, are well-preserved in lake sediments. Preservation of remains might even differ among cladoceran species with Bosmina and chydorid well represented by different body part (Frey, 1988) in contrast to Daphnia which are usually under-represented in sediment samples compared to Bosmina (Frey, 1960;Kattel et al, 2007;Kattel, 2009;Nykänen et al, 2009).…”
Section: Introductionmentioning
confidence: 83%
“…Despite their usefulness, relatively few quantitative paleolimnological studies of Cladocera have been completed on Ontario lakes (e.g. Hann, 1981;Smol & Boucherle, 1985;Boucherle et al, 1986;Hann et al, 1994;Tremel et al, 2000;St. Jacques et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The cladocerans display morphological variability (cyclomorphosis) in food web. Vertebrate predation pressure on Bosmina, for example can result in variation in size of the mucro (Hann et al, 1994). In temperate arid Australia, Daphnia carinata show a cyclomorphic behaviour with seasonal changes in body size.…”
Section: Management Of Food Webmentioning
confidence: 99%